Interaction and Interrelation in Social Enterprise Between Entrepreneurship and Social Issues - Yang, Chang-Lin; Huang, Kai-Ping; Tosompark, Chanikarn; Suwanmana, Piyanan; Chuang, Wen-Bin (KINERJA, 2022)
Social enterprises have gained attention in recent decades. Many universities, private institutions, and government agencies promote social enterprises to solve social problems and create social value. Social entrepreneurship can be materialized in two ways: one from social issues to entrepreneurship and the other from entrepreneurship to social issues. The process from social issues to entrepreneurship is mainly concerned with assisting individuals, disadvantaged groups, or communities in addressing social issues in relation to establishing social enterprises. The process from entrepreneurship to social issues leads existing enterprises or entrepreneurs to explore social issues that may reveal economic opportunities and create social enterprises. This study focuses on these two types of social entrepreneurship and attempts to determine differences between the entrepreneurship and business model, characteristics and entrepreneurial spirits, and social impact. This study employs comprehensive thinking, collation, and analysis of different management patterns and content patterns of social enterprises to understand the different entrepreneurial styles. This study found that social enterprises created from social issues to entrepreneurship were more concerned with other people's problems. Their funding appeared less reliant on earning and repayment. The resources were more diverse. Such social enterprises might focus their care on people or communities they missioned to help and not practice profit or surplus distribution to shareholders. On the contrary, social enterprises from entrepreneurship to social issues were inspired by their own issues. A large part of such social enterprises' funding might be from earnings or repayment. Such social enterprises might involve fewer volunteers, make less use of free services, focus on exchanges of products or services for repayment, and distribute profit or surplus to shareholders.